A Multi-Centre Prospective Study of the Efficacy and Safety of Alglucosidase Alfa in Chinese Patients With Infantile-Onset Pompe Disease - Zhu, Diqi; Zhu, Jiacong; Qiu, Wenjuan; Wang, Benzhen; Liu, Lin; Yu, Xiaodan; Ou, Zhenheng; Shan, Guangsong; Wang, Jian; Li, Bin; Chen, Xiaokang; Liu, Cong; et al. (Frontiers in Pharmacology, 2022)
Background: A high prevalence of infantile-onset Pompe disease (IOPD) in the Chinese population has been noted, but there are currently no reported clinical trials of enzyme replacement therapy (ERT) for IOPD in this population. The purpose of this study was to evaluate the efficacy and safety of alglucosidase alfa in Chinese patients with IOPD. Materials and Methods: A multicentre, single-arm, prospective, open-label clinical trial was performed at 4 sites in China. Eligible Chinese subjects with IOPD received an infusion of alglucosidase alfa at a dose of 20 mg/kg every 2 weeks for up to 52 weeks. The primary endpoints of clinical efficacy were the survival rate and changes in the left ventricular mass index (LVMI). The safety assessment was based on the incidence of adverse events (AEs). Results: A total of 10 eligible subjects were enrolled in the study. The mean age at the start of ERT was 5.36±1.56 months. Nine subjects had survived after 52 weeks of treatment. One subject discontinued the study and died after mechanical ventilation was withdrawn. The intent-to-treat analysis demonstrated that the survival rate was 90.0% (95% confidence interval: 55.5%-99.7%). The mean LVMI at week 52 was 70.59±39.93 g/m2 compared to that of 298.02±178.43 g/m2 at baseline, with a difference of -227.60±155.99 g/m2. All subjects had left ventricular mass (LVM) Z scores > 10 at baseline, and eight subjects (80%) achieved Z scores < 5 at week 52. No treatment-related AEs were observed, and no AEs led to the discontinuation of treatment. Conclusions: This clinical trial is the first study of ERT for IOPD in China, indicating that alglucosidase alfa has favourable efficacy and safety for the treatment of Chinese patients with IOPD (ClinicalTrials.gov number, NCT03687333).